(untitled) - Marx, Leo (New York, 1964)
For over four decades, Leo Marx's work has focused on the relationship between technology and culture in 19th- and 20th-century America. His research helped to define--and continues to give depth to--the area of American studies concerned with the links between scientific and technological advances, and the way society and culture both determine these links. The Machine in the Garden fully examines the difference between the "pastoral" and "progressive" ideals which characterized early 19th-century American culture, and which ultimately evolved into the basis for much of the environmental and nuclear debates of contemporary society.
Keywords: Công nghệ,Technology; Khía cạnh xã hội,Social aspects; Hoa Kỳ,United States